HYDRO ENERGY AND ENVIRONMENTAL POLICIES IN TURKEY - Yuksel, Ibrahim; Arman, Hasan; Serencam, Ugur (YILDIZ TECHNICAL UNIV, 2016)
Hydro energy is a renewable, sustainable and clean energy in the other alternative energy sources. Moreover, it does not deprive future generations in terms of raw materials, or burdening them with pollutants or waste. Hydroelectric power plants utilize the basic national and renewable resource of the country. Although the initial investment cost of hydropower seems relatively high, the projects have the lowest production costs and do not depend on foreign capital and support, when considering environmental pollution and long-term economic evaluation. Hydropower is available in a broad range of project scales and types. Projects can be designed to suit particular needs and specific site conditions. As hydropower does not consume or pollute the water it uses to generate power, it leaves this vital resource available for other uses. At the same time, the revenues generated through electricity sales can finance other infrastructure essential for human welfare. This can include drinking water supply systems, irrigation schemes for food production, infrastructures enhancing navigation, recreational facilities and ecotourism.
Keywords: Hydropower; Renewable energy; Clean Energy; Environmental Policies; Turkey; CLIMATE-CHANGE MITIGATION; SUSTAINABLE DEVELOPMENT; BIOMASS; IMPACTS; FUTURE; Thermodynamics